DAF-16/FOXO and HLH-30/TFEB function as combinatorial transcription factors to promote stress resistance and longevity - Xin-Xuan Lin (Nature Portfolio, 2018)
The transcription factor DAF-16/FOXO is a downstream effector of insulin/insulin-like growth factor signaling and plays an important role in stress resistance and longevity. Here, the authors show that DAF-16/FOXO can form a complex with HLH-30/TFEB to synergistically regulate transcription of target genes in response to certain stress stimuli.